Productivity and economics of rice cultivars under different irrigation regimes and systems of cultivation - GV, Venkataravana Nayaka; G, Prabhakara Reddy; Kumar R, Mahender (ORYZA-An International Journal of Rice, 2021)
Shortage of water in rice cultivation is major problem in India. To safeguard and sustain food security in India, it is quite important to increase the productivity of rice under limited water resources. To investigate the performance of rice cultivars under the best method of irrigation and system of cultivation in new condition an experiment was conducted to study the "productivity and water use efficiency of rice (Oryza sativa L.) cultivars under different irrigation regimes and systems of cultivation" on clay loam soils of Indian Institute of Rice Research (IIRR), Rajendranagar, Hyderabad, Telangana during the kharif seasons of 2017 and 2018. The treatment comprised of two irrigation regimes viz., AWD and saturation as main plot treatments, three establishment methods viz., system of rice intensification, drum seeding and TP as subplot treatments and four cultivars namely DRR Dhan 42, DRR Dhan 43, MTU-1010 and NLR-34449 as sub-sub plot treatments summing up to 24 treatment combinations laid out in split-split plot design with three replications. Among the irrigation regimes, AWD irrigation practice recorded higher grain yield (5755, 5952 and 5854 kg ha-1 in 2017, 2018 and pooled means, respectively) than saturation. Among the different systems of cultivation, the SRI recorded significantly higher grain yield (5953, 6129 and 6041 kg ha-1 during 2017, 2018 and in pooled means, respectively) over the TP method. Among the different rice cultivars, DRR Dhan 43 registered remarkably higher grain yield than other cultivars during 2017 and 2018.